2000
DOI: 10.1175/1520-0442(2000)013<4087:acopfi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Census of Precipitation Features in the Tropics Using TRMM: Radar, Ice Scattering, and Lightning Observations

Abstract: An algorithm has been developed to identify precipitation features (Ն75 km 2 in size) in two land and two ocean regions during August, September, and October 1998. It uses data from two instruments on the Tropical Rainfall Measuring Mission (TRMM) satellite: near-surface precipitation radar (PR) reflectivities, and TRMM Microwave Imager (TMI) 85.5-GHz polarization corrected temperatures (PCTs). These features were classified by size and intensity criteria to identify mesoscale convective systems (MCSs), precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
403
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 374 publications
(428 citation statements)
references
References 30 publications
22
403
0
3
Order By: Relevance
“…Consistent with past literature [e.g., Nesbitt et al, 2000;Liu, 2011], precipitation systems tend to be larger over the ocean than over land (Figure 4a). However, organized convective regions (CFs) tend to be larger over land than over the ocean (Figure 4b).…”
Section: Global Distribution and Morphologysupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with past literature [e.g., Nesbitt et al, 2000;Liu, 2011], precipitation systems tend to be larger over the ocean than over land (Figure 4a). However, organized convective regions (CFs) tend to be larger over land than over the ocean (Figure 4b).…”
Section: Global Distribution and Morphologysupporting
confidence: 90%
“…[10] During 1998-2011, more than 28 million RPFs and 21 million CFs are identified from the TRMM PR observations over 36 S-36 N, most of which are over the ocean ( Table 1 RPFs and CFs are similar to and consistent with past studies [Nesbitt et al, 2000;Liu et al 2008] and are not shown here. We mainly focus on describing the properties of the CFs with large areas in the following sections.…”
Section: Global Distribution Of Organized Convectionsupporting
confidence: 75%
See 2 more Smart Citations
“…[13] This study is based on precipitating features (storm scale), using the 11 years long TRMM precipitation feature (PF) database [Nesbitt et al, 2000;Liu et al, 2008]. Lightning data are from observations by the TRMM LIS, while thunderstorm parameters are based on measurements from the TRMM precipitation radar (PR) and microwave imager (TMI).…”
Section: Methodsmentioning
confidence: 99%